Can a Green Tax Reform Entail Employment Double Dividend in European and non-European Countries? A Survey of the Empirical Evidence - Maxim, Maruf Rahman; Zander, Kerstin (International Journal of Energy Economics and Policy, 2019)
This paper synthesises the simulation studies concerning green tax reform (GTR) and employment double dividend (EDD) in European and non-European countries. The studies included investigate the effect of GTR on employment. We compared the simulation results between European and non-European countries to understand the impact of study region and our findings are fivefold. First, the simulation results suggest that GTR-driven EDD is observed in both European and non-European countries, but the average effect on employment in European countries (0.67%) is significantly greater than in non-European countries (0.18%). Second, optimal tax and tax revenue recycling policies in European and non-European countries for EDD are not identical. Reducing employers’ social security contributions (SSC) has the potential to generate EDD in both countries. However, a reduction in value added tax (VAT) has the highest average effect on employment in European countries (1.62%), which negatively affects employment in non-European countries (-0.02%). Third, a reduction in personal income tax (PIT) as a tax recycling method creates a marginally average employment dividend in non-European countries (0.16%) but is counterproductive in European countries (-0.15%). Fourth, other taxes, which predominantly represent mixed taxes, exhibit the highest EDD potential in both European (1.01%) and non-European (0.46%) countries. Finally, employment dividend diminishes over time, but a weak quadratic pattern has been observed that reveals an accelerating effect on employment in the long term. These reflections should be considered before employing GTR in non-European countries in order to yield EDD. Keywords: Green tax reform, Double dividend, Employment JEL Classifications: H23, H21, E24 DOI: https://doi.org/10.32479/ijeep.7578